2015
DOI: 10.1073/pnas.1423542112
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying seasonal population fluxes driving rubella transmission dynamics using mobile phone data

Abstract: Changing patterns of human aggregation are thought to drive annual and multiannual outbreaks of infectious diseases, but the paucity of data about travel behavior and population flux over time has made this idea difficult to test quantitatively. Current measures of human mobility, especially in low-income settings, are often static, relying on approximate travel times, road networks, or crosssectional surveys. Mobile phone data provide a unique source of information about human travel, but the power of these d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
122
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(126 citation statements)
references
References 35 publications
1
122
2
1
Order By: Relevance
“…In the context of infectious disease spread in developing countries, this new source of information enables previously unseen kinds of analyses. Examples are the derivation of magnitude and destination of population fluxes following a sudden outbreak (25,31), and the quantification of the importance of human mobility and its seasonal variations on the spread of disease in terms of increased outbreak risk in and infectious pressure on connected areas (5,30,(32)(33)(34).…”
mentioning
confidence: 99%
“…In the context of infectious disease spread in developing countries, this new source of information enables previously unseen kinds of analyses. Examples are the derivation of magnitude and destination of population fluxes following a sudden outbreak (25,31), and the quantification of the importance of human mobility and its seasonal variations on the spread of disease in terms of increased outbreak risk in and infectious pressure on connected areas (5,30,(32)(33)(34).…”
mentioning
confidence: 99%
“…Differential ownership of mobile phones among different sectors, particularly in low and middle income countries where much of CDR research takes place, also calls into question the representativeness of the data and thus the findings that ensue [72]. However, it has also been observed that despite biases, there a few, if any, data sources that can provide such rich spatial and temporal movement data, particularly for much-needed research in LMICs [61,64].…”
Section: Discussion Principal Findings: Opportunities and Challengesmentioning
confidence: 99%
“…Where this data is available, and particularly where it can be combined with data on seasonal disease incidence, there is potential for considerable advances in understanding the role played by human movement in shaping seasonal disease dynamics. Previous work has suggested, for example, that seasonal mobility in Kenya shapes the magnitude of transmission of rubella [50], which has implications in turn for spatial dynamics of the infection, and can determine the burden of Congenital Rubella Syndrome [51]. Likewise, predictive frameworks for dengue outbreaks are more accurate when they incorporate both climatic variations and human movements measured by mobile phones [52], allowing for vector control and hospital preparation in advance of epidemics.…”
Section: New Approaches To Understanding Seasonalitymentioning
confidence: 99%